Modeling and control of a doubly fed induction generator with a disturbance observer: a stator voltage oriented approach - Özsoy, Emre E.; Golubovic, Edin; Şabanoviç, Asif; Boğosyan, Seta; Gökaşan, Metin (The Scientific and Technological Research Council of Turkey (TUBITAK-ULAKBIM) - DIGITAL COMMONS JOURNALS, 2016)
The popularity of renewable energy conversion systems, and especially of wind energy, has been growing in recent years. Doubly fed induction generator (DFIG)-based wind energy systems are extensively used due to their wide range of active and reactive power controllability. Conventional DFIG control structures consist of decoupled PI rotor current controllers with stator flux orientation and machine parameter-dependent compensating terms. The accuracy of stator flux calculations is dependent on how accurately the stator resistance is known. Integration problems also exist and additional low-pass filters are implemented to accurately calculate the stator flux. In the current study, machine-dependent compensating terms are estimated with a rst-order low-pass filter disturbance observer. Therefore, a single proportional (P) controller is sufficient to control decoupled rotor currents. The proposed controller structure is implemented on a MATLAB/Simulink platform with the parameters of 500 kW DFIG used in the M_ILRES (Turkish National Wind Energy) project. The proposed controller is also experimentally validated in an experimental setup.
Keywords: TK1-4661 Electrical engineering. Electronics Nuclear engineering; TK7800-8360 Electronics; TK Electrical engineering. Electronics Nuclear engineering